The magnetic instability of Yb2Pd2(In,Sn) in a non-Fermi liquid environment - Bauer, E.; Hilscher, G.; Michor, H.; Paul, Ch.; Aoki, Y.; Sato, H.; Adroja, D.T.; Park, J.-G.; Bonville, P.; Godart, C.; Sereni, J.G.; Giovannini, M.; et al. (IOP Publishing, 2005)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina